PENGARUH PENAMBAHAN JENIS BAHAN PAKAN SUMBER PROTEIN PADA RANSUM BERBASIS HIJAUAN KELAPA SAWIT TERHADAP KECERNAAN BAHAN KERING DAN BAHAN ORGANIK PADA KELINCI LOKAL JANTAN - Nugroho, Alden Imawan; ,, Muhtarudin; Widodo, Yusuf (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The purpose of this study was to find out the effect of feed protein resources addition in ration based on waste and forage from palm tree against digestibleness of dry substanceÂ  and organic substance in rabbit male local. This study uses a randomizedÂ  group design with three treatments and four groups. Rabbits used were a local male rabbits with a body weight range group 1) 210- 250g, group 2) 260-300g, group 3) 310-350 g group 4) 360-400 g. The treatments were given in this study is R0 = basal diet (0.3% of palm fibers, palm leaf green 0.7% and 27% of palm treeâs oil cake, bran 32%, corn 40%), R1 = R0 + 15% cassava leaves, R2 = R1 + 3% chicken feather meal. Data`s Â were tested using analysis of variance and continued with Least Significant Difference test. The results showed that the addition of feed protein resources addition in the ration, based on waste and palm treeâs forage significantly affect on digestibility of dry substanceÂ  and organic substance in rabbit male local. Forage-based feed waste andÂ  palm tree plus hydrolyzedÂ  protein source from chicken feather mealÂ  (R2) were the best treatment for digestibleness of dry substance and organic substance of local male rabbits. KeywordsÂ Â Â  : Cassava Leave, Chicken Flour Hydrolyzate, Local Male Rabbits, Palm Oil Waste and Forage, Rabbits Dry Matter Digestibility and Organic Materials.